Dysregulation of Iron Metabolism in Alzheimer's Disease, Parkinson's Disease, and Amyotrophic Lateral Sclerosis - Satoru Oshiro; Masaki S. Morioka; Masataka Kikuchi (Hindawi Limited, 2011)
Dysregulation of iron metabolism has been observed in patients with neurodegenerative diseases (NDs). Utilization of several importers and exporters for iron transport in brain cells helps maintain iron homeostasis. Dysregulation of iron homeostasis leads to the production of neurotoxic substances and reactive oxygen species, resulting in iron-induced oxidative stress. In Alzheimer's disease (AD) and Parkinson's disease (PD), circumstantial evidence has shown that dysregulation of brain iron homeostasis leads to abnormal iron accumulation. Several genetic studies have revealed mutations in genes associated with increased iron uptake, increased oxidative stress, and an altered inflammatory response in amyotrophic lateral sclerosis (ALS). Here, we review the recent findings on brain iron metabolism in common NDs, such as AD, PD, and ALS. We also summarize the conventional and novel types of iron chelators, which can successfully decrease excess iron accumulation in brain lesions. For example, iron-chelating drugs have neuroprotective effects, preventing neural apoptosis, and activate cellular protective pathways against oxidative stress. Glial cells also protect neurons by secreting antioxidants and antiapoptotic substances. These new findings of experimental and clinical studies may provide a scientific foundation for advances in drug development for NDs.